MANAGERIAL PERFORMANCE OF VILLAGE ADMINISTRATION - Vita Mayastinasari (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
The village government is a milestone in achieving governance that is closest to the community. This has the potential to increase public trust in government. However, this is a challenge for village officials to regulate the running of government at the village level, so that the managerial skills of village officials are very important for every village official to have. The purpose of this research is to describe the managerial performance of village administration in Banyumas Regency. The method used is a survey approach with data collection, namely questionnaires, observation and documentation. The sample technique used is multi-stage sampling with 81 respondents selected based on geographical location. Each item in the questionnaire has been tested to be valid and reliable based on the r count value which is greater than the r table. The results show that the managerial apparatus of the village in managing government in Banyumas Regency is in a good category. This is shown by the existence of good planning, organizing, actuating, and controling of village government. Keywords; Managerial Performance, Governance, Village Government.